Implementation of Expert System For Insomnia Diagnosis With Uncertainty Method - Suryati Suryati; Suzan Agustri (Proceeding International Conference on Information Technology and Business, 2020)
The growing information and communication technology had expanded into various fields (e.g., the field of medicine). Various software products had been widely produced to support the needs of consumers, especially the products related to expert systems that were able to assist experts in addressing various problems. The expert system was one of the artificial intelligence engineering areas that were highly demanded by consumers because this application was proven to be very helpful in solving certain problems in the field of science and business. Insomnia was not a disease, but a symptom that had several causes (e.g., emotional abnormalities, physical abnormalities, the use of medication, or the presence of disturbances from the area around the residence ranging from noises that interfered with the ears or the influence of weather). Therefore, the expert system development was able to assist the public to identify the types of symptoms of insomnia by applying uncertainty methods to the expert system either in diagnosing or finding problems, which had never previously been found.Keywords: Technology, Expert System, Insomnia, Uncertainty, Method